Protective effects of dietary Ocimum basilicum and Thymus vulgaris essential oils on growth performance, immune response, and disease resistance following challenge with Aeromonas hydrophila in Nile Tilapia (Oreochromis niloticus) - Salah M. Aly; Heba M. A. Abdelrazek; Nada H. Eidaroos; Samar I. Mostafa; Doaa S. Farid; Noha I. ElBanna; Mohamed Fathi (Fish Physiology and Biochemistry, 2026)

Corrigendum to “Photocatalytic degradation of reactive blue 19 and antibacterial efficacy utilizing a magnetically separable C-doped TiO₂/copper-lead ferrite nanocomposite” [J. Water Process Eng. 82 (2026) 1–15 (109535)] - Doaa F. Baamer; Elsayed T. Helmy; H.G. Mohamedbakr; Amr.M. Elbasiony; Mohamed Mokhtar M. Mostafa (Journal of Water Process Engineering, 2026)

Integrating sustainability in green supply chains: Optimizing carbon emissions and operational efficiency - Mina Fahim; Mohamed Grida; Mostafa Ashour; Doaa Naeem (Environmental Impact Assessment Review, 2026)

Photocatalytic degradation of reactive blue 19 and antibacterial efficacy utilizing a magnetically separable C-doped TiO₂/copper-lead ferrite nanocomposite - Doaa F. Baamer; Elsayed T. Helmy; H.G. Mohamed Bakr; Amr.M. Elbasiony; Mohamed Mokhtar M. Mostafa (Journal of Water Process Engineering, 2026)

Protective effect of abietic acid nanoparticles synthesized by gamma-irradiation against cisplatin-induced renal injury in mice: a promising novel natural nano-drug - Mostafa Saif-Elnasr; Doaa S. Salah-Eldin; Alshimaa M. Elmalawany; M. A. Elhady; Heba K. Abdelhakim (Molecular Biology Reports, 2025)

Targeting the sigma-1 receptor with pridopidine induces functional neurorestoration in spinal cord ischemia-reperfusion injury - Eman Sweed; Suzan A. Khodir; Shaimaa Mohamed Motawea; Hala El-Haron; Basma Abdelnaby Mostafa; Mona S. Elkholy; Mohammud Salim; Doaa Z. M. Shebl (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Spinal cord ischemia reperfusion injury (IRI) occurs with an incidence of 1–32%, often leading to paraplegia with limited prevention options. Pridopidine (Prdpn), a highly selective sigma-1 receptor (Sig-1R) agonist, serves as a protein chaperone that is engaged in neuroplasticity and cellular defense. This research aimed to assess the neuroprotective properties of Prdpn in spinal cord IRI in rats and investigate the underlying mechanisms. Forty male Wistar albino rats were randomly allocated into 4 groups: control, sham, IRI, and IRI + Prdpn. Tarlov’s test was used to examine behavioral performance, as well as withdrawal from agonizing stimuli and the placing/stepping reflex (SPR). Biochemical markers, including spinal malondialdehyde (MDA), AOPP, antioxidant GPX, TNF-α and IL-1β, and apoptotic caspase-3, were measured, along with BDNF, GDNF, and Sig-1R gene expression. Histopathological changes in spinal cord tissue were also evaluated. Spinal cord IRI significantly caused neurological deficits, evidenced by lower scores in Tarlov’s test, withdrawal from agonizing stimuli, and SPR. Biochemically, spinal cord IRI led to decreased GPX and increased MDA, AOPP, TNF-α, IL-1β, caspase-3, and GDNF levels, along with downregulated BDNF and Sig-1R gene expression. Histopathologically, spinal cord IRI resulted in greater spinal neuronal degeneration, apoptosis, and demyelination. However, treatment with Prdpn significantly improved behavioral outcomes and partially reversed the biochemical and histopathological alterations. Prdpn improved spinal cord IRI-induced behavioral deficits through its antioxidant, anti-inflammatory, anti-apoptotic, and neurotrophic properties. It suggests promise as a potential treatment option to stop spinal cord IRI.

Acetamiprid-induced pulmonary toxicity via oxidative stress, epithelial-mesenchymal transition, apoptosis, and extracellular matrix accumulation in human lung epithelial cells and fibroblasts: Protective role of heat-killed Lactobacilli - Samah S. Arafa; Heba A. Elnoury; Sahar Badr El-Din; Mohamed A. Sakr; Fatma Fawzi Hendawi; Rehab Ali Elsayed Masoud; Samia Soliman Barghash; Doaa Sabry Elbehairy; Ayat Abdelaty Hemeda; Islam Mostafa Farrag; Doaa Sayed Abdelrahman; Amira Mohammad Elsadek; et al. (Food and Chemical Toxicology, 2025)

Valorization of abattoir water discharge through phycoremediation for enhanced biomass and biodiesel production - Mahdy Elsayed; Yevheniia Mysnyk; Mohamed Mahmoud-Aly; Ehab Mostafa; Adel W. Almutairi; Doaa G. Abbas; Mohamed M. Ibrahim; Dieter Hanelt; Abdelfatah Abomohra (Biomass and Bioenergy, 2024)

Global Potato Production Forecasting Based on Time Series Analysis and Advanced Waterwheel Plant Optimization Algorithm - Amel Ali Alhussan; Doaa Sami Khafaga; Mostafa Abotaleb; Pradeep Mishra; El-Sayed M. El-Kenawy (Potato Research, 2024)

Forecasting Production of Potato for a Sustainable Future: Global Market Analysis - Pradeep Mishra; Amel Ali Alhussan; Doaa Sami Khafaga; Priyanka Lal; Soumik Ray; Mostafa Abotaleb; Khder Alakkari; Marwa M. Eid; El-Sayed M. El-kenawy (Potato Research, 2024)

The Role of Chlorella vulgaris in Attenuating Infertility Induced by Cadmium Chloride via Suppressing Oxidative Stress and Modulating Spermatogenesis and Steroidogenesis in Male Rats - Mayada R Farag; Nesma I. El-naseery; Eman I. El behery; Doaa S. Nouh; Amany El-Mleeh; Ismail M.A. Mostafa; Mahmoud Alagawany; Alessandro Di Cerbo; Mahmoud M. Azzam; Suzan A. Mawed (Biological Trace Element Research, 2024)

Optimizing Potato Disease Classification Using a Metaheuristics Algorithm for Deep Learning: A Novel Approach for Sustainable Agriculture - El-Sayed M. El-Kenawy; Amel Ali Alhussan; Doaa Sami Khafaga; Mostafa Abotaleb; Pradeep Mishra; Reham Arnous; Marwa M. Eid (Potato Research, 2024)

The potential protective effect of Camellia Sinensis in mitigating monosodium glutamate-induced neurotoxicity: biochemical and histological study in male albino rats - Walaa G. Abdelhamid; Noha A. Mowaad; Gihan F. Asaad; Asmaa F. Galal; Sarah S. Mohammed; Olfat E. Mostafa; Doaa R. Sadek; Lobna A. Elkhateb (Metabolic Brain Disease, 2024)
Monosodium glutamate (MSG) is the sodium compound derived from glutamic acid. Excessive daily ingestion of MSG leads to elevated amounts of glutamic acid in the bloodstream, which can be detrimental to brain structures. Camellia sinensis, often known as green tea (GT), is a rich source of essential hexogen antioxidants that are necessary for the body. Thirty-two adult male albino rats were divided into four groups ( n = 8). Group 1 served as a control -ve group. Group 2 was given GT (1.5 ml/rat/day). Group 3 was given MSG (600 mg/kg/day). Group 4 was given MSG (600 mg/kg/day) and GT (1.5 ml/rat/day). All treatments were given orally for 28 days. MSG administration resulted in significant neurotoxicity in rats that was revealed by the significant reduction of serum concentration of glutathione peroxidase (GPx) and nitric oxide (NO), and the significant elevation of total antioxidant capacity (TAC) accompanied by the significant reduction of levels of serum monoamines (dopamine, serotonin, and norepinephrine) and histological changes in the hippocampus area CA1, dentate gyrus, and cerebellar cortex and positive immunohistochemical staining of glial fibrillary acidic proteins (GFAP) and calretinin. Administration of GT with MSG counteracted the MSG-mediated oxidative stress by significantly increasing serum concentrations of GP X and NO and significantly decreasing concentrations of TAC. Furthermore, GT significantly increased levels of serum monoamines (dopamine, serotonin, and norepinephrine). Moreover, it ameliorated the histological changes, GFAP, and calretinin immunostaining in brain tissues. It is envisaged that GT will serve as a viable protective choice for the inclusion of the neurotoxicity treatment procedure.

Differential Physiological and Molecular Processes in the Root May Underlie Contrasting Salt Tolerance in Two Egyptian Rice Cultivars at the Seedling Stage - Ahmad Mohammad M. Mekawy; Dekoum V.M. Assaha; Jiacheng Li; Asmaa Yusuf; Doaa Mostafa; Mahmoud Ali Shoulkamy; Akihiro Ueda (Journal of Soil Science and Plant Nutrition, 2024)
This study aimed to compare various responses of two Egyptian rice accessions bred for high yields, Sakha108 and Giza177, to salt stress at the seedling stage. Twenty-eight-day-old seedlings of two cultivars were grown in a hydroponic medium under control conditions (no NaCl) and salt stress (75 mM NaCl) for 12 days. Growth (dry weight), Na + and K + concentrations, enzymatic and non-enzymatic antioxidants, malondialdehyde (MDA), hydrogen peroxide (H 2 O 2 ), and expression of Na + and K + transport-coding genes were recorded. Sakha108’s growth (18% rise from control) was significantly higher than Giza177’s. Both cultivars accumulated similar amounts of Na + in the leaves and sheaths, however, Sakha108 had higher Na + concentrations in the roots than Giza177 (13.3% higher). Root K + concentration dropped dramatically (~ 2-fold reduction) in Giza177 roots while remaining unchanged in Sakha108 roots. The concentrations of H 2 O 2 (root) and MDA (leaf and root) were higher in Giza177 than in Sakha108, although the difference was not statistically significant. Proline and total flavonoid (TF) contents in Sakha108 roots were greater than those in Giza177 roots. The expression of OsHKT1;5 and OsHKT2;1 genes declined in both cultivars, whereas expressions of OsSOS1 , OsNHX1 , and OsHAK7 were induced in Sakha108 but, except for OsHAK7 , were repressed in Giza177. Combined, these findings suggest that Sakha108 is more resistant to salt stress than Giza177 is, and that this variation in tolerance may have its origins in the root systems of the two cultivars. Thus, these adaptive traits in the root of Sakha 108 could be explored for engineering stress tolerance in susceptible but high-yielding rice cultivars.

Resveratrol protects against Schistosoma mansoni-induced liver fibrosis by targeting the Sirt-1/NF-κB axis - Dalia Kamal Mostafa; Maha M. Eissa; Doaa A. Ghareeb; Shaymaa Abdulmalek; Wafaa A. Hewedy (Inflammopharmacology, 2024)
Hepatic schistosomiasis is a prevalent form of chronic liver disease that drastically affects human health. Nevertheless, an antifibrotic drug that could suppress the development of hepatic fibrosis does not exist yet. The current study aimed to evaluate the effect of resveratrol, a natural polyphenol with multiple biological activities, on Schistosoma mansoni ( S. mansoni )-induced hepatic fibrosis and delineate the underlying molecular mechanism. Swiss male albino mice were randomly assigned into infected and non-infected groups. Hepatic schistosomiasis infection was induced via exposure to S. mansoni cercariae. 6 weeks later, resveratrol was administrated either as 20 mg/kg/day or 100 mg/kg/day for 4 weeks to two infected groups. Another group received vehicle and served as infected control group. At the end of the study, portal hemodynamic, biochemical, and histopathological evaluation of liver tissues were conducted. Remarkably, resveratrol significantly reduced portal pressure, portal and mesenteric flow in a dose-dependent manner. It improved several key features of hepatic injury as evidenced biochemically by a significant reduction of bilirubin and liver enzymes, and histologically by amelioration of the granulomatous and inflammatory reactions. In line, resveratrol reduced the expression of pro-inflammatory markers; TNF-α, IL-1β and MCP-1 mRNA, together with fibrotic markers; collagen-1, TGF-β1 and α-SMA. Moreover, resveratrol restored SIRT1/NF-κB balance in hepatic tissues which is the main switch-off control for all the fibrotic and inflammatory mechanisms. Taken together, it can be inferred that resveratrol possesses a possible anti-fibrotic effect that can halt the progression of hepatic schistosomiasis via targeting SIRT1/ NF-κB signaling.

Current progress toward synthetic routes and medicinal significance of quinoline - Wesam S. Shehab; Mostafa M. K. Amer; Doaa A. Elsayed; Krishna Kumar Yadav; Magda H. Abdellattif (Medicinal Chemistry Research, 2023)
Quinoline motifs are essential in several pharmacological active heterocyclic compounds due to their various applications in medicinal and industrial chemistry. Furthermore, there are greater societal expectations in the current scenario that synthetic and medicinal chemists should produce greener and more sustainable chemical processes. Therefore, this mini-review article highlights the traditional and green synthetic approaches of quinoline and its analogs, including multicomponent one-pot reactions and solvent-free reaction conditions utilizing microwave and ultraviolet irradiation-promoted synthesis using eco-friendly and safe reusable catalysts, in addition to discussing the medicinal importance of quinoline derivatives such as anticancer, antioxidant, anti-inflammatory, antimalarial, anti-SARS-CoV-2, and antituberculosis activities within the period from 2011 till 2021. Therefore, the quinoline scaffolds signify a unique class of pharmacophores present in various therapeutic agents.

An integrated strategy combining UPLC-MS/MS, chemometrics, molecular docking, and molecular dynamics simulation for metabolic profiling of onion (Allium cepa L.) cultivars and unravelling potential anti-COVID-19 metabolites - Mariam M. Elattar; Hala M. Hammoda; Doaa A. Ghareeb; Mostafa F. El-Hosseny; Mohamed G. Seadawy; Ismail Celı̇k; Reham S. Darwish; Hend M. Dawood (South African Journal of Botany, 2023)

Acidified Compost and Silymarin-Enriched Bio-Stimulators Integratively Improve Morpho-Physio-Biochemistry, Antioxidant Capacity, and Polyamine Metabolism Enzymes of Atriplex Nummularia Lindl Seedlings Under Saline-Calcareous Conditions - Mostafa M. Rady; Hesham F. Alharby; Doaa’ A. M. M. Tarfayah; Safia M. A. Ahmed (Journal of Soil Science and Plant Nutrition, 2023)

Correction: Irisin improves adiposity and exercise tolerance in a rat model of postmenopausal obesity through enhancing adipo-myocyte thermogenesis - Rehab E. Abo El Gheit; Reham L. Younis; Mervat H. El-Saka; Marwa N. Emam; Nema A. Soliman; Rehab M. El-Sayed; Yasser Mostafa Hafez; Norhan Ahmed AbuoHashish; Doaa A. Radwan; Howayda E. Khaled; Samar Kamel; Sawsan A. Zaitone; et al. (Journal of Physiology and Biochemistry, 2023)

Carnosic Acid Mitigates Depression-Like Behavior in Ovariectomized Mice via Activation of Nrf2/HO-1 Pathway - Doaa M. Samy; Dalia Kamal Mostafa; Samar R. Saleh; Passainte S. Hassaan; Teshreen M. Zeitoun; Gamal A. G. Ammar; Nahed H. Elsokkary (Molecular Neurobiology, 2023)
The peri- and post-menopausal periods have been described as the “window of vulnerability” for the development of depressive symptoms that impair women activities and quality of life. The etiopathogenesis of these symptoms is multifactorial and may confer resistance to traditional antidepressants. Attention is now directed toward phytochemicals for their pleiotropic functions and safer profiles. This study investigated the possible perturbation of the nuclear factor erythroid 2–related factor 2 (Nrf2) signaling pathways as an underlying mechanism of post-ovariectomy depression and highlighted the potential benefits of carnosic acid (CA) on the associated behavioral, biochemical, and histopathological alterations. Female Balb/c mice were randomly assigned to be sham-operated or ovariectomized (OVX). After 3 weeks, OVX mice received either a vehicle, CA (20 mg/kg/day), or tin protoporphyrin IX (SnPP-IX; a heme oxygenase-1 (HO-1) inhibitor; 50 μmol/kg/day) for 3 weeks. Our findings revealed that OVX mice had depressive but not anxiety-like behavior. Suppressed Nrf2 and its downstream signaling, and augmented proinflammatory markers were observed in both the hippocampus and prefrontal cortex. CA treatment alleviated depressive behavior, induced the expression of Nrf2, HO-1, thioredoxin-1, and brain-derived neurotrophic factor, and enhanced serotonin levels. CA also suppressed oxidative stress, reduced TNF-α, IL-1β, and iNOS mRNA expression, and ameliorated OVX-induced histopathological changes. SnPP-IX aggravated post-OVX behavioral, neurobiochemical, and histological deteriorations, and reduced CA-protective effects. In conclusion, Nrf2/HO-1 signaling suppression and the associated proinflammatory state are key mechanisms in post-OVX depression. CA exerts multifaceted neuroprotection in OVX mice and represents a promising candidate for clinical evaluation as an antidepressant.

Irisin improves adiposity and exercise tolerance in a rat model of postmenopausal obesity through enhancing adipo-myocyte thermogenesis - Rehab E. Abo El Gheit; Reham L. Younis; Mervat H. El-Saka; Marwa N. Emam; Nema A. Soliman; Rehab M. El-Sayed; Yasser Mostafa Hafez; Norhan Ahmed AbuoHashish; Doaa A. Radwan; Howayda E. khaled; Samar Kamel; Sawsan A. Zaitone; et al. (Journal of Physiology and Biochemistry, 2022)
The prevalence of obesity and its associated metabolic disorders, along with their healthcare costs, is rising exponentially. Irisin, an adipomyokine, may serve as a critical cross-organ messenger, linking skeletal muscle with adipose tissue and the liver to integrate the energy homeostasis under diet-induced obesity. We aimed to explore the putative role of irisin in the protection against obesity in a postmenopausal rat model by modulating energy expenditure (EE). Bilateral ovariectomy (OVX) was performed. After 3 weeks of recovery, the OVX rats were classified according to their dietary protocol into rats maintained on normal diets (ND) (OVX) or high-fat diet (HFD) groups. The HFD-fed animals were equally divided into OVX/HFD, or irisin-treated OVX/HFD groups. Sham rats, maintained on ND, were selected as the control group. We evaluated anthropometric, EE, and molecular biomarkers of browning and thermogenesis in inguinal white adipose tissue and skeletal muscle, and the activity of the proteins related to mitochondrial long chain fatty acid transport, oxidation, and glycolysis. HFD of OVX further deteriorated the disturbed glucose homeostasis, lipid profile, and the reduced irisin, thermogenic parameters in adipose tissue and skeletal muscle, and EE. Irisin treatment improved the lipid profile and insulin resistance. That was associated with reduced hepatic gluconeogenic enzyme activities and restored hepatic glycogen content. Irisin reduced ectopic lipid infiltration. Irisin augmented EE by activating non-shivering thermogenesis in muscle and adipose tissues and decreasing metabolic efficiency. Our experimental evidence suggests irisin’s use as a potential thermogenic agent, therapeutically targeting obesity in postmenopausal patients. Graphical abstract Irisin modulates the non-shivering thermogenesis in skeletal muscle and adipose tissue in postmenopausal model

Modeling COVID-19 effects on SDGs using system dynamics in Egypt - Mohamed Marzouk; Shimaa Azab; Nehal Elshaboury; Alaa Megahed; Mahmoud Metawie; Mostafa El Hawary; Doaa Ghaith; AbdElMoniem Bayoumi (Environmental Science and Pollution Research, 2022)
The coronavirus disease 2019 (COVID-19) poses a significant threat to achieving the Sustainable Development Goals (SDGs). To address this challenge, a thorough examination of the pandemic’s influence on four SDGs in Egypt is presented in a system dynamic model. The addressed goals are related to no poverty (SDG 1), zero hunger (SDG 2), decent work and economic growth (SDG 8), and climate action (SDG 13). The model is simulated over 35 years extending from 2015 to 2050. Furthermore, a web-based interactive learning environment is developed to analyze the interdependencies among public health activities and study the impacts of possible intervention countermeasures or prevention policies. Indicators including poverty line, food insecurity, gross domestic product (GDP) growth rate, and greenhouse gas (GHG) emissions are evaluated to track Egypt’s performance in relation to SDGs 1, 2, 8, and 13. According to the simulation model, the poverty line will continue to decline until it reaches around 16% by 2050. According to the significant governmental efforts to follow its vision of 2030, Egypt can achieve a decreasing percentage of food insecurity, reaching 3% in 2030, and this percentage will continue to decrease until it reaches full sufficiency by 2050. The GDP growth rate will rise every year until it reaches 13.71% in 2050. With respect to climate, GHG emissions are predicted to fall to roughly 97 Mt CO2-equivalents by 2050. This approach revitalizes debates about the achievement of SDGs amid the crisis and acts as a powerful tool that aids decision-makers in identifying leverage points to avoid the long-term negative repercussions of the crisis on the economy, people, and environment.

Radioactivity and mineralogical studies with an emphasis on recovery of thorium from mylonite rocks in the Abu Rusheid area, South Eastern Desert, Egypt - Mohamed Salem Kamar; Ahmed Rabea Bakry; Lamia Abdelrahman Yousef; Doaa Anwar Mostafa (Euro-Mediterranean Journal for Environmental Integration, 2020)

Source rock evaluation of subsurface Devonian–Carboniferous succession based on palyno-organic facies analysis in Faghur Basin, North Western Desert of Egypt: a division of the North Africa Paleozoic Basins - Esam A. Abd El Gawad; Mohamed F. Ghanem; Walid A. Makled; Doaa A. Mousa; Mostafa M. Lotfy; Mostafa G. Temraz; Amr M. Shehata (Arabian Journal of Geosciences, 2019)

Industrial oil wastewater treatment by free and immobilized Aspergillus niger KX759617 and the possibility of using it in crop irrigation - Eman H. F. Abd El-Zaher; Alaa M. Abou-Zeid; Azza A. Mostafa; Doaa M. Arif (Rendiconti Lincei. Scienze Fisiche e Naturali, 2017)

Differential metformin dose-dependent effects on cognition in rats: role of Akt - Dalia K. Mostafa; Cherine A. Ismail; Doaa A. Ghareeb (Psychopharmacology, 2016)